Responsible fishing in the Indian ocean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The recently launched South West Indian Ocean Fisheries Commission (SWIOFC) aims to promote responsible fishing